The Work of Maternity and Infant Welfare Centres - Labour Party (Great Britain). Advisory Committee on Public Health
1926-01 1926 1920s 7 pages - 6 - (121b) In addition, there are maternal abnormalities, deformities, and poisonings of the system the effects of which correct and timely supervision might mitigate. In the case of the pregnant woman, "to be forewarned is to be forearmed" and if Ante-Natal Clinics were linked up with Maternity Homes, and in close touch professionally with doctors and midwives, and established throughout the country, the coming generation of mothers would be freed from many ills. The Ante-Natal Clinic, worked in its entirety, provides the expectant mother with advice; in normal cases giving re-assurance of security and lessening any disabilities, and providing dental treatment when necessary; in other cases detecting abnormalities and where there are poisonings of the system (such as from alcohol, lead, syphilis, etc.) sending for treatment to hospital. After child-birth the Clinic should be satisfied that the mother's health is normal. To obtain an increasing number of women for attendance during pregnancy, extensive education in what is called the "New Midwifery" should be given by all Health Visitors and Centre Nurses by means of lectures and conversation. It goes without saying that the doctor in charge of the Ante-Natal Clinic (man or woman) should be experienced in the preventive side of obstetrics and have a working knowledge of the psychology of pregnancy. The clinic should have attached to it the services of "Home Helps" to do household duties in the home during the lying-in of all mothers too poor to pay a neighbour to help, or so situated that no relative can efficiently look after mother and babe, and other children. Only about 50 local authorities and 9 Voluntary Centres make any provision for the employment of "Home Helps." Much ill-health could be avoided if these Helps were appointed in larger numbers. There would not be so many cases where the mother sits up in bed washing clothes or attending to the needs of the other children before the new-born baby is many days old, for she would rest properly when her house was managed by a 292/824/1/135